Possibilidades de atuação da terapia ocupacional junto a universitários com quadro de adoecimento mental: um relato de experiência - LIMA, Jessica Monique Furtado (2023)
INTRODUCTION: The university student experiences different situations during his academic experience, and when external factors or internal to the university environment trigger a process of mental illness, this circumstance can cause problems for his occupational performance. OBJECTIVE: To describe the lived experience of occupational therapeutic practices in an extension project with university students with suspected or diagnosed mental illness. METHODOLOGY: It is a work of qualitative approach and it is an experience report covering the practices lived through an extension project carried out in a university located in the city of Belém, where it covered the period between March and December of 2017. The study's target audience was composed of eight undergraduate students from a university in the city of Belém. The report aims to describe the performance of Occupational Therapy in the area of mental health aimed at the university student who presented a sickness mental. As instruments used for the collection of information, the following construction was carried out: Diário de Campo, Reception Form, Occupational Therapeutic Assessment Form in Mental Health and Occupational Therapeutic Plan. RESULTS AND DISCUSSION: The experience in the extension project allowed a significant amount of experiences during its development. Different strategies were developed for the development of actions. The initial strategy consisted of the active search, where activities of dissemination about the project and the importance of attention to mental health were carried out. The process was initiated by the reception of the university, where the clarification and the collection of information pertinent to the definition of the occupational profile of the participant was carried out. When identified problems in occupational performance related to a mental illness, it was referred to the Occupational Therapy Evaluation in Mental Health, with the purpose of identifying demands and the occupational history of the student. Related aspects were identified during the visits to students regarding self-esteem, social interaction and occupational routine. Based on the information gathered, an intervention plan was developed, defining objectives and proposals for approaches and techniques that could be used. However, although there is currently a significant amount of research aimed at the university student, a small amount of research was found relating the actions of occupational therapeutics to the university environment. FINAL CONSIDERATIONS: The actions developed by the project showed the relevance of the offer of services directed to university students. It also highlights the importance of raising awareness and clarifying the importance of mental health care and broadening the discussion of the issue. Keywords: Occupational Therapy; Mental health; Student; University.